Modifying the mechanical properties of silk nanofiber scaffold by knitted orientation for regenerative medicine applications - Dodel, M; Hemmati Nejad, N; Bahrami, S H; Soleimani, M; Hanaee-Ahvaz, H (Cellular and Molecular Biology, 2016)
Tissue reconstruction is among the increasing applications of polymer nanofibers. Fibrous scaffolds (mats) can be easily produced using the electrospinning method with structure and biomechanical properties similar to those of a cellular matrix. Electrospinning is widely used in the production of nanofibers and the GAP-method electrospinning is one of the means of producing fully aligned nanofibers. In this research, using the GAP-method, knitted fibrous scaffolds were made of silk fibroin, which is a biocompatible and biodegradable polymer. To extract fibroin from cocoons, the sodium chloride solution as well as dialysis and freeze-drying techniques were employed. The molecular weight of the extracted fibroin was measured with the SDS-Page electrophoresis technique. Moreover, the pure fibroin structure was examined using the ATR-FTIR method, and the viscosity of the solution used for electrospinning was measured with the Brookfield rotational viscometer. The scaffolds were prepared through electrospinning of the silk fibroin in pure formic acid solution. The following three structures were electrospun: 1) a random structure; 2) a knitted structure with an interstitial angle of 60 degrees; 3) a knitted structure with an interstitial angle of 90 degrees. Morphology of the resulting fibers was studied with a SEM (scanning electron microscope). Fibroin scaffolds are degradable in water. Therefore, they were fixated through immersion in methanol to be prepared for assays. The mechanical properties of the scaffolds were also studied using a tensile strength test device. The effect of methanol on the strength properties of the samples was also assessed. The hydrophilic potential of the samples was measured via a contact angle test. To increase the hydrophilicity of the scaffold surfaces, the cold oxygen plasma technique was employed. Finally, the biocompatibility and cell adhesion of the resulting scaffolds were examined through a HEK 293 cell culture, and the results were analyzed through the MTT, DAPI staining, and SEM imaging techniques. Results revealed that the oriented knitted structure contributed to the increase in Young's modulus and the maximum strength of scaffolds as compared to the random samples. Moreover, this structure can also be a suitable alternative to the typical chemical means of increasing strength.